III.yy. da kariyer yapmış olan Küçükasya kökenli Roma senatörleri - Ertekin, Efrumiye (My University, 2002)
OF THESIS ROMAN SENATORS FROM ASIA MINOR WHO HAD TAKEN UP A CAREER IN THE THIRD CENTURY A.D. This research, the aim of which is to bring to light the gravity of Senators from Asia Minor in the administration of Roman Empire from the quality and quantity points of view, is constituted in two main part: The Prosopografic Part and The Hitorical Part. In the Prosopographic Part that is based on geographical origin, all sources concerning each senator are given openly; then prosopographics and literature are given in a list, and explanations relating to each senator are made on the light of sources and literature. In the Historical Part, interpretations are made from four points of view: At first, it is dwelled on that the dispersion of the Senators accoding to regions and cities and the factors that determine this dispersion. Second, family origins of Senators are brought out; then it is dwelled on careers of senators. Finally, it is taken up how a dispersion of the senators is according to the dynasties. At the result of this interpretations, it was determined that the integration of the provincial aristocracy of Asia Minor into the Roman senatorial rank had taken place in three distinct phases: Under the Julio-Claudians the descendants of Italian setters (veterans and merchants), in the Flavian- Trajanic period the descendant of the native royal houses, in the period from Hadrian to the end of third century the native upper clases of the cities were accepted to the Senat. Typically different are also the urban origins of the three group: The former Italians came from the colonies of the strongly romanized countries; the senators of royal ancestry came from the old residences such as Pergamum and Ankyra; the local aristocracy was present everywhere except in the less urbanised eastern part of Asia Minor. From about 260 senators who took a career in the Principate, 105 Senators in the first and the second century, the rest 155 senators took a career in the third century. 17 per cent of senators who took a career in the first and second century and 30 per cent of in the third century are without degree. This situation shows that on the contrary of numeric increase in the third century, the number of qualified senator lessened. However, it is necesary to considering this situation, not as the quality loss of Senator from Asia Minor, but generally decreas of gravity of senatorial rank in the administration, and as the reflection of this general situation to Senators from Asia Minor. The period of Severus' especially the period of Septimius Severus and Caracalla is the most resplendent period of Senators from Asia Minor. In this Period, Senators from Asia Minor became about 20 per cent of all Roman Senators and 60 per cent of provincial senators.
Keywords: Tarih Eskiçağ